2018
DOI: 10.1038/s41598-018-29731-w
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-like protein 4 (ANGPTL4) is related to gestational weight gain in pregnant women with obesity

Abstract: Angiopoietin-like protein 4 (ANGPTL4) is a circulating protein involved in the regulation of adipose tissue metabolism. However, its role in obesity and pregnancy is unknown. To evaluate the relationship between gestational weight gain (GWG) and circulating concentrations of ANGPTL4 in pregnant women with overweight and obesity, weight gain and fasting maternal blood samples of thirty-one pregnant women was drawn at 15, 24 and 32 weeks of gestation. ANGPTL4 concentrations continuously rose throughout gestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“… 38 , 39 However, the predictive model also highlighted a set of proteomic features with no known inflammatory properties that were correlated with features from the inflammatory module. These proteins included protein-arginine deiminase type II (PADI2), a peptidylarginine deiminase that is responsible for protein citrullination and implicated in parturition and sensing infections 40 , 41 ; transferrin receptor (TfR), which is implicated in iron transport; angiopoietin-like 4 (ANGPTL4), which regulates glucose homeostasis and lipid metabolism 42 ; and RARRES2, an adipokine that is increased in metabolic syndrome and gestational diabetes. 43 , 44 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 38 , 39 However, the predictive model also highlighted a set of proteomic features with no known inflammatory properties that were correlated with features from the inflammatory module. These proteins included protein-arginine deiminase type II (PADI2), a peptidylarginine deiminase that is responsible for protein citrullination and implicated in parturition and sensing infections 40 , 41 ; transferrin receptor (TfR), which is implicated in iron transport; angiopoietin-like 4 (ANGPTL4), which regulates glucose homeostasis and lipid metabolism 42 ; and RARRES2, an adipokine that is increased in metabolic syndrome and gestational diabetes. 43 , 44 …”
Section: Resultsmentioning
confidence: 99%
“…angiopoietin-like 4 (ANGPTL4), which regulates glucose homeostasis and lipid metabolism 42 ; and RARRES2, an adipokine that is increased in metabolic syndrome and gestational diabetes. 43,44 To ascertain whether observed correlations between these proteins and the inflammatory module reflected biologically relevant inflammatory properties, we examined the capacity of each of these factors to stimulate human peripheral blood leukocytes using an ex vivo mass cytometry assay.…”
Section: Predictive Modeling Of Ptbmentioning
confidence: 99%
“…Notably, plasma ANGPTL4 levels significantly increased after weight gain and decreased after weight loss [ 60 ]. In addition, an increase in plasma ANGPTL4 throughout pregnancy was positively associated with gestational weight gain and could be used as an early marker of increased susceptibility to excess gestational weight gain [ 66 ].…”
Section: Angptl3 and Glucose Homeostasis ( Figure 2 mentioning
confidence: 99%
“…127 In pregnant subjects with excess body mass, increasing blood angiopoietin-like protein 4 level throughout pregnancy is associated positively with gestational weight gain and can serve as a marker of susceptibility to excess gestational weight gain, whereas plasma leptin and VEGF do not show such a trend. 128 A study of Leijnse et al demonstrated that leptin may be even associated with pregnancy outcome: Overweight women with adverse pregnancy outcomes had elevated circulating leptin level accompanied with impaired placentation and reduced placental vascularization; no such relationship was found for VEGF. 129 In women with excess body mass and preeclampsia, the serum level of leptin, though not of VEGF or hypoxia-inducible factor 1 (HIF-1), is higher than in BMI-matched subjects without preeclampsia.…”
Section: Human Studiesmentioning
confidence: 99%